Characterization and evaluation of Pugal Sheep in the home tract - DASS, GOPAL (The Indian Journal of Animal Sciences, 2011)
Pugal, a sheep breed of north-western arid and semi-arid region of the country, is mainly found in Bikaner district of Rajasthan. Animals are known for good mothering ability and adapted to harsh climate. The population of this breed has tremendously declined due to usage of breeding rams of Magra sheep of the same habitat. The least squares averages of morphometric traits viz. body length, height at withers, chest girth, ear length and tail length ranged from 32.76±O.24 to 63.20±O.43, 39.36±0.28 to 62.88±O.31, 35.64±0.28 to 73.63±O.63, 6.35±O.08 to 9.41±O.20 and 12.75±O.16 to 18.23±O.17 cm in different sex and age groups, body weights at birth, 3, 6,12 months and in adults were 2.62±O.01, 17.92±O.07, 23.55±O.ll, 29.74±0.28 and 38.88±O.28 kg. The greasy fleece weights in first, second, third and total annual clips were 558, 513, 549 and 1618 g, wool quality parameters, viz. fibre diameter, hetro and hairy fibres, medullation, staple length and crimp were 34.42±O.45Jl, 28.l9±O.67%, 30.94±1.22%, 59.14±1.37%, 6.07±O.O.13 cm and O.77±O.03/cm. Milk production on 7th and 50th day of lactation was 249.21±4.14 and 112.20±11.87 g. Weight at slaughter, weight of skin, length of skin, weight of head, weight of liver, weight of kidney, weight of empty digestive tract, weight of legs, weight of carcass and dressing per cent were 22.73±O.27 kg, 3.30±O.08 kg, 57.03±O.37 cm, L44±O.03 kg, 354.00±7.64 g, 75.17±1.69 g, 1.63±O.02 kg, 2.82±O.05 kg, 9.97±O.l7 kg and 43.77±O.45%. The reproduction traits, viz. age at first oestrus, oestrus cycle duration, oestrus duration, age at first lambing, gestation length, service period, lambing percentage and lambing interval were 10.15±O.05 nl0nth, 15.28±O.05 days, 23.12±O.l8 h, 15.47±.07 month, 153.38±O.45 days, 93.24±O.88 days, 98.12±4.25% and 283.13±0.95 days, respectively. The breed is significantly contributing to the livelihood of the people due to its good migration capability and overall performance. Therefore, sincere efforts are needed immediately for its improvement and conservation.